2018
DOI: 10.1021/jacs.7b11125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bi3+ Heterovalent Doping in Organic–Inorganic Metal Halide Perovskite Crystals

Abstract: Intrinsic organic-inorganic metal halide perovskites (OIHP) based semiconductors have shown wide applications in optoelectronic devices. There have been several attempts to incorporate heterovalent metal (e.g., Bi) ions in the perovskites in an attempt to induce electronic doping and increase the charge carrier density in the semiconductor. It has been reported that inclusion of Bi decreases the band gap of the material considerably. However, contrary to the earlier conclusions, despite a clear change in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
207
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(238 citation statements)
references
References 27 publications
29
207
0
2
Order By: Relevance
“…Heterovalent alloying has been studied in many other materials and is known to have a variety of effects on the host material, including modulating carrier concentrations, 11 altering the kinetics of phase transformation, 12,13 lowering the ferroelectric transition temperature, 13 inducing disorder and vacancies, 14,15 and affecting ionic conductivity. 12,14 Although there have been numerous attempts at incorporating small amounts of monovalent and trivalent metals into the lead perovskites, [16][17][18][19][20][21][22][23][24][25][26][27] detailed experimental characterization of the resulting materials that provide a thorough understanding of the structural and electronic changes in the alloys are still needed. A recent study with a computational focus explored Pb 2+ alloying of 1, which resulted in a ca.…”
Section: Introductionmentioning
confidence: 99%
“…Heterovalent alloying has been studied in many other materials and is known to have a variety of effects on the host material, including modulating carrier concentrations, 11 altering the kinetics of phase transformation, 12,13 lowering the ferroelectric transition temperature, 13 inducing disorder and vacancies, 14,15 and affecting ionic conductivity. 12,14 Although there have been numerous attempts at incorporating small amounts of monovalent and trivalent metals into the lead perovskites, [16][17][18][19][20][21][22][23][24][25][26][27] detailed experimental characterization of the resulting materials that provide a thorough understanding of the structural and electronic changes in the alloys are still needed. A recent study with a computational focus explored Pb 2+ alloying of 1, which resulted in a ca.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] It has been shownt hat the introduction of heterovalent Bi 3 + into methyl bromide based perovskite (MAPbBr 3 )p recursor solutionsc ould lead to charge doping of MAPbBr 3 . [19][20][21] The success in Bi 3 + -based doping benefits from the ease of Bi 3 + entering the octahedral cages becauseo ft he analogous electronic structures of Bi 3 + with Pb 2 + and an appropriate Goldschmidt tolerance factor (0.889). [20,22] As ar esult,t he lattice structure in MAPbBr 3 hosts can be favorably maintained by partially substituted Pb 2 + with Bi 3 + .H owever,t he necessity of Bi 3 + doping has been challenged by the recent finding by Snaith et al [19] that the introduced heterovalent Bi 3 + dopants may result in the formation of impurity states in the perovskite crystal, which can serve as an onradiative recombination center.…”
Section: Introductionmentioning
confidence: 99%
“…[20,22] As ar esult,t he lattice structure in MAPbBr 3 hosts can be favorably maintained by partially substituted Pb 2 + with Bi 3 + .H owever,t he necessity of Bi 3 + doping has been challenged by the recent finding by Snaith et al [19] that the introduced heterovalent Bi 3 + dopants may result in the formation of impurity states in the perovskite crystal, which can serve as an onradiative recombination center. [19,23] As ar esult, the PL lifetimea nd carrierd iffusion length are impaired. In addition, the impact of Bi 3 + doping on the favored photon recycling effect (PRE) has been investigated by Yamada et al [21] It was found that the powerc onversion efficiency became considerably weakened after Bi 3 + doping, due to the shortened PL lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…A report of partial replacement of Pb 2+ with Sr 2+ demonsrated that the short‐circuit current density and the fill factor could be improved effectively . Trivalent metal ions doping (Al 3+ , Bi 3+ , Sb 3+ , In 3+ ) is beneficial to the crystal growth of perovskite films with suppressed microstrain and reduced defects . And monovalent cations of Cu + , Na + , and Ag + were also introduced into the CH 3 NH 3 PbI 3 to tune the morphological, optical, and electrical properties of perovskite films .…”
Section: Introductionmentioning
confidence: 99%